Covid-19 Full-Dose Vaccination across Uninsured Populations: Evidence across Counties in the United States - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the propensities of the U.S. population to seek a full dose of vaccinations against the COVID-19 pandemic. Beyond the consideration of vaccine dissemination at the disaggregated or the local level, the main focus of this study is on determining whether a lack of health insurance significantly impacted vaccination propensities. If it is indeed the case that a lack of health insurance mattered, this would be informative for policymakers since they tried to address this aspect in the vaccine rollout by subsidizing and offering vaccines at a zero price. Our results show that the uninsured were less likely to be fully vaccinated against the pandemic and this finding holds across different modeling formulations. However, there were differences in the responses of the different population subgroups. The findings with respect to the vaccination propensities of the unvaccinated are noteworthy, especially significant given the fact the COVID-19 vaccines were made available free of cost to the public in the United States, irrespective of their insurance status. A policy lesson from these results is that perhaps a better outreach to communities of the uninsured to inform them about the costs and availability of the coronavirus vaccines would have been better. Interestingly, new covid cases did not significantly impact decisions to fully vaccinate, while greater prosperity made full vaccination more likely. We did not find robust evidence of the elderly having a greater propensity to be fully vaccinated. Finally, accounting for the political dimension, counties housing the seats of the state government had greater full vaccination rates, ceteris paribus.
Keywords: I18; I13; I11; H75; G22; 330; Covid-19; vaccination; pandemic; insurance; elderly; county; United States